(untitled) (Research, Society and Development, 2021)
Research with the insertion of cover crops in the Amazon region is still scarce and necessary for the viability of the system of succession, rotation and/ or no-tillage. However, the present work aimed to evaluate the biomass production and nutrient absorption by different cover crops in the absence and presence of phosphate fertilization, as well as to verify the effects of straw on the productivity of common bean cultivated in the second crop, since the type of straw present in the soil surface can influence crop management. The experiment was conducted in field conditions, in the experimental area of the Federal Institute of Education, Science and Technology of Rondônia, Campus Colorado do Oeste, in the municipality of Western Colorado, RO. The experimental design used was randomized blocks, arranged in a 4 x 2 x 4 scheme, consisting of the planting of four cover species (Crotalária spectabilis, Crotalária ochroleuca, Mucuna cinza and Feijão guandu) two doses of phosphorus (0 and 80 kg ha-1 of P2O5) and four replications. The results allowed to conclude that the species Crotalaria ochroleuca and Crotalaria spectabilis have great potential for dry matter production. The production components of the common bean present better results in succession to green fertilization with Crotalaria ochroleuca and Mucuna Cinza. The dose of phosphorus applied under the cover plants favored, in addition to the absorption of P and K, the absorption of other nutrients, such as Ca and Mg, which, through the decomposition and mineralization of their residues, were able to meet part of the nutritional demand of the bean crop.